Load Balance: Energy Efficient Routing Protocol in Wireless Sensor Network - A. Mohamed Divan Masood; S. K. Muthusundar (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Energy  consumption  is  one  of  the  major  issue  in Wireless Sensor Network  (WSN)  which reduces the lifetime of the network. In this developed work an  Cluster based Energy Efficient Routing Protocol (CBEERP) , which is  gathering the sensor hubs  in the system  into  clusters,  in this manner it productively decreased the flooding  traffic  during  discover the routing. The proposed CBEERP will balance the Energy in the Group by using some second order nodes. The reinforcement High effective hubs replace the cluster head after the cluster reaches to its threshold energy level. This CBEERP will help the effectiveness and lifetime of the system.